Patient perspectives of recovery after hip fracture: a systematic review and qualitative synthesis. Issue 21 (9th October 2022) - Beer, Natasha; Riffat, Aleena; Volkmer, Brittannia; Wyatt, David; Lambe, Kate; Sheehan, Katie J.
Abstract: Purpose: The purpose of the current review is to synthesize the evidence of patients' perspectives of recovery after hip fracture across the care continuum. Methods: A systematic search was conducted, focusing on qualitative data from hip fracture patients. Screening, quality appraisal, and a subset of articles for extraction were completed in duplicate. Themes were generated using a thematic synthesis of data from original studies. Results: Fourteen high-quality qualitative studies were included. Four review themes were identified: recovery as participation, feelings of vulnerability, driving recovery, and reliance on support. Patients considered recovery as a return to pre-fracture activities or "normal" enabling independence. Feelings of vulnerability were observed irrespective of the time since hip fracture and only diminished when recovery of function and activities enabled participation in valued activities, e.g., outdoor mobility. Participants expressed a desire to engage in recovery with realistic expectations and the benefits of meaningful feedback reported. While reliance on healthcare professionals decreased towards a later stage of recovery, reliance on social support persisted until recovery was perceived to have been achieved. Conclusion: Patient perspectives highlighted hip fracture as a major life event requiring health professional and social support to overcome feelings of vulnerability and enable active engagement in recovery. IMPLICATIONS FOR REHABILITATION: Rehabilitation professionals should ensure expectations and goals are set early in the recovery process. Rehabilitation professionals should ensure goals set with patients are tailored to the individual's pre-fracture activities or "normal" promoting independence. Rehabilitation professionals should monitor goals ensuring they are providing support, motivation, and managing expectations across the care continuum. Rehabilitation professionals should address patients' feelings of vulnerability, particularly in the absence of social support, and ensure appropriate ongoing input to maximize recovery.